Midland non‐invasive ventilation score: a tool to predict non‐invasive ventilation failure in people with acute hypercapnic respiratory failure. Issue 11 (20th November 2020) - Quigley, David; Jones, Simon; Piccolo, Francesco; Huseini, Taha; Manners, David
Abstract: Use of non‐invasive ventilation (NIV) in patients with hypercapnic respiratory failure has clear benefits over invasive ventilation. Existing risk prediction models are complex and difficult to apply in the acute setting. We developed the Midland NIV score comprising only five parameters for use to predict NIV failure (in‐hospital death or intubation) at initiation. Individuals with Midland NIV score of ≤11 (average 13% NIV failure) may be suitable for general ward care, compared to intensive care for those with Midland NIV score ≥12 (average 66% NIV failure rate). Prospective external validation is required.